Factors associated with medication adherence among children with rheumatic diseases - Manatpreeprem, Roongroj; Lerkvaleekul, Butsabong; Vilaiyuk, Soamarat (Frontiers in Pharmacology, 2023)
Introduction: Failure to take medications regularly leads to poorer health outcomes. The Pediatric Rheumatology Adherence Questionnaire (PRAQ) is an effective tool for assessing medication adherence in rheumatic patients. Therefore, we aimed to determine the factors associated with poor medication adherence among children with rheumatic diseases. Methods: This was a cross-sectional study. Patients with rheumatic diseases who had taken at least one medication and had been followed up at our pediatric rheumatology clinic were included in the study, together with their caregivers. Patients with poor medication adherence were characterized as those who had taken less than 80% of their prescribed drugs, as determined using the pill count method. The original PRAQ was translated and validated in Thai language and was completed by caregivers and literate patients over age 13 years. Interviewing for additional problems with taking medications was conducted. We performed descriptive and logistic regression analyses. Results: From 210 patients, 52.86% had juvenile idiopathic arthritis (JIA), and 46.19% had connective tissue diseases. The mean patient age was 14.10±4.74 years, with a median (interquartile range) disease duration of 4.33 (2.08–6.98) years. PRAQ scores in the group with poor adherence were significantly higher than scores in the group with good adherence (11.00±3.47 vs. 9.51±3.16, P=0.004). Enthesitis-related arthritis (ERA) (odds ratio [OR] 9.09, 95% confidence interval [CI] 1.25–66.18; P=0.029) and polyarticular JIA (OR 6.43, 95% CI 1.30–31.75; P=0.022) were associated with poor treatment adherence. Disease duration ≥5 years (OR 3.88, 95% CI 1.17–12.87; P=0.027), active disease (OR 6.49, 95% CI 1.76–23.99; P=0.005), PRAQ scores ≥12 (OR 6.48, 95% CI 1.76–23.82; P=0.005), forgetting to take medications (OR 14.18, 95% CI 4.21–47.73; P <0.001), and unawareness about the importance of the medicines (OR 44.18, 95% CI 11.30–172.73; P <0.001) were predictors of poor drug adherence. Conclusions: In the present study, poor medication adherence was found in one-fourth of children with rheumatic illnesses, particularly those with ERA, polyarticular JIA, longer disease duration, active disease, and high PRAQ scores. The most frequent reasons for inadequate medication adherence were forgetfulness and unawareness about the importance of disease control and consistency with treatment.